NEW DERMATOLOGICAL INDICATIONS FOR PULSED DYE LASERS - Natalia Jiménez Gómez; Bibiana Pérez García; Pablo Boixeda; Pedro Jaén (European Medical Journal, 2015)
Laser therapy has been classically focussed on three different chromophores: haemoglobin, melanin, and water, based on selective photothermolysis theory. Despite the fact that therapy is evolving with the introduction of multiple new wavelengths and the description of more therapeutic targets, some laser devices, such as the pulsed dye laser (PDL), are still relevant in our clinical practice. Based on a redefined concept of selective photothermolysis, PDL seems to be a promising tool for the treatment of skin conditions different to vascular lesions. Its role in viral infections, inflammatory diseases (such as acne or systemic lupus erythematosus), scars, and basal cell carcinoma is reviewed in this paper.